Five-Year Bibliometric Analysis of Education 4.0 and Direction for Education 5.0 Future Research - Nur Balqishanis, Zainal Abidin; Nur Amalina, Mat Jan; Ainin Zakiah, Othman; Loshini, Thiruchelvam; Lim, Shun Jinn; Sarah A’fifah, Abdullah Sani; Nurul Ikma, Haris; Nurhanim, Abdul Aziz (International Journal of Learning, Teaching and Educational Research, 2023)
Education 4.0 is a conceptual education framework for current generations. The evolution of education has continued to evolve, which in turn creates a research niche for innovation development in higher education institutions. This study aimed to analyse articles on Education 4.0 research from 2018 to 2022 using the Scopus database as well as identifying current trends in the field of education. This research examined trends in publication and citation performance, journal-related performances, most frequently cited articles, top affiliated countries, and emerging research trends. A bibliometric study was employed in achieving the objectives of the study, guided by five research questions. The study began by extracting metadata and analysing keyword co-occurrence using VOSviewer software and Microsoft Excel. Results showed that Malaysia, Mexico, and Indonesia are three of the top countries to which authors who publish about Education 4.0 research are affiliated. It was also found that there were five emerging research trends related to Education 4.0, namely (a) Education 4.0 on various educational mechanisms, features, and applications; (b) the effect of COVID-19 on the engineering education learning system and the role of Education 4.0; (c) Education 4.0 by means of modern information technologies; (d) developing a framework for innovation in Education 4.0, and (e) technology and digital transformation in Education 4.0. Two suggestions are also made for the direction of future study. Lastly, the implication of this bibliometric study on Education 4.0 informs and shapes the direction of the upcoming Education 5.0 research.